Exploring Modifications to Individual Trauma-Focused PTSD Treatments in a Routine Care Setting: An Examination of Medical Records at a Veterans Health Administration PTSD Clinic. Issue 4 (November 2022) - Williston, Sarah Krill; Kruepke, Michael; Grossman, Daniel; Litwack, Scott; Niles, Barbara L.
Highlights: Modifications document the delivery of trauma-focused treatments to 131 veteran–clinician pairs in an urban PTSD clinical setting using the adapted FRAME. Modifications to trauma-focused treatments were reported in over 60% of veteran–clinician pairs. Common modifications included spreading (27%), repeating (24%), drift with return (22%), and integrating (21%). A large portion of veterans continued to engage in care following TF-EBT engagement. Abstract: Clinicians in naturalistic settings regularly modify the delivery of trauma-focused treatments to enhance client engagement and retention. However, what types of modifications are made in clinical settings, why, and when, and their impact on client outcomes has seldom been examined. As an initial step to address this, the current study applied elements of the updated Framework for Reporting Adaptations and Modifications—Expanded (FRAME; Wilstey Stirman et al., 2019) to examine content-level modifications documented in the delivery of posttraumatic stress disorder (PTSD) treatment to veterans via medical records review in an urban PTSD clinic. Results indicated that the updated FRAME suited the data well, and that modifications occurred in most veteran–clinician pairs over the course of treatment. The four most common modifications documented were spreading (27%), repeating (24%), drift with return (22%), and integrating (21%). Three composite case examples are discussed that describe the application of the most common modifications observed in medical record documentation. This is an important first step toward understanding the real-world modifications of evidence-based trauma-focused interventions that in turn will lead to critical recommendations for improving treatment implementation.